Dadgummit [large type] - Toussaint, Maggie (Toussaint, Maggie. Dreamwalker mystery, 2018)
During a family vacation at a mountainside lake, psychic sleuth Baxley Powell is enlisted by the local police to find the killer of a man mysteriously drained of his life force. The otherworldly trail leads to Jonas, a vampire who feeds off energy.